Hubungan Pengetahuan, Asupan Natrium, dan Status Gizi Dengan Kejadian Hipertensi Di Poli Lansia Puskesmas Kecamatan Ciracas - Tri Ardianti Khasanah; Muslimah, Nur Fitriani (Media Gizi Ilmiah Indonesia, 2023)
Hypertension is referred to as the silent killer because it often occurs without complaints, so that sufferers do not know they have the disease and only find out after complications occur. Most of the elderly people are at risk of developing hypertension. The purpose of the study is to analyze the relationship between knowledge, sodium intake, and nutritional status with incidence of hypertension in Elderly Polyclinic Ciracas Sub-District Health Center. The research design used descriptive analytic with a cross-sectional study approach involving 62 research subjects. Data collected in the form of questionnaires, anthropometric measurements, and blood pressure measurements. The statistical analysis used was the chi-square test. The results showed that there were (56.5%) research subjects suffering from hypertension. The results of the chi-square test showed that there was a relationship between knowledge (p-value = 0.031), sodium intake (p-value = 0.037), and nutritional status (p-value = 0.107) with the incidence of hypertension. The conclusion in this study is that knowledge and sodium intake are associated with the incidence of hypertension, but there is no relationship between nutritional status and the incidence of hypertension.